Evaluasi Kegiatan Digital Marketing PT AkzoNobel Car Refinishes Indonesia di Platform Instagram - Brigitta Valentina Jessica; Imam Syafganti (Lembaga Pengembangan Kinerja Dosen, 2024)
The growth of modern technology has brought about numerous changes and new developments. Things that were previously considered unimaginable are now seen as commonplace and intriguing to many people. One example is the internet. Digitization can now be applied to all types of businesses, from the smallest to the largest. The formulation of marketing strategies has become more effective with this digitization. This study aims to examine the digital marketing activities of PT AkzoNobel Car Refinishes Indonesia on the Instagram social media platform. The research is conducted to review the uploaded content, engagement with followers, and their impact on the brand and sales. Data were obtained from direct experience during the internship process at the company. Research has shown that with proper and effective use, Instagram has provided considerable excitement for the company and its managers to utilize.